Orthostatic Hypotension and Cerebral Perfusion in Falls and Related Syncopal Disorders - Claffey, Paul James (Trinity College Dublin. School of Medicine. Discipline of Medical Gerontology, 2025)
Falls, syncope and orthostatic dizziness are common reasons for hospital presentations and are highly prevalent among older adults, leading to significant morbidity, loss of independence and increased healthcare utilisation. These problems may indicate impairments in mechanisms regulating systemic blood pressure (BP) and cerebral blood flow (CBF). Orthostatic Hypotension (OH) is defined by consensus statement as a sustained drop in systolic BP of at least 20 mmHg or in diastolic BP of at least 10 mmHg, within 3 minutes of standing. OH is associated with several adverse health outcomes including falls. Current practice involves measuring peripheral beat-to-beat BP and heart rate (HR) during active standing and head up tilt (HUT) two potent physiological stressors to the cardiovascular system providing valuable information for diagnosis and management. However, less is known about CBF during these stressors, particularly in older adults who may or may not report symptoms of cerebral hypoperfusion. Near-Infrared Spectroscopy (NIRS) is a non-invasive technology that measures frontal lobe cerebral tissue oxygenation, known as tissue saturation index (TSI) regarded as a suitable surrogate for CBF and can be applied during clinical orthostatic BP assessment. The primary aim of this thesis is to investigate the relationship between CBF and OH in two cohorts: a clinical group of patients with falls, syncope and dizziness recruited from a specialised outpatient setting and a population group of participants from The Irish Longitudinal Study on Ageing (TILDA). The hypothesis was that OH would be associated with greater cerebral hypoperfusion upon standing and would explain symptoms of orthostatic intolerance. Furthermore, it was hypothesised that degree of cerebral hypoperfusion would inform future falls risk. Four hundred ninety-one patients attending a national referral clinic had concurrent TSI recorded alongside peripheral beat-to-beat BP during an active stand (AS). The prevalence of OH was 38.5%. OH patients experienced greater declines in TSI compared to those without. Mixed-effects linear regression models demonstrated a significant relationship between OH and TSI at the same timepoint ( -0.53, [95% confidence interval (CI) -0.59 - -0.46]; p<0.001), which persisted following adjustment for age, sex, baseline BP, cerebrovascular and cardiovascular disease, depression/ anxiety, diabetes, systolic BP, antihypertensives, and antidepressants ( -0.51, [CI -0.58 - -0.44]; p<0.001). TSI changes did not differ in those with symptomatic OH versus those with asymptomatic OH. Secondly, the TILDA population study of over 900 community-dwelling individuals aged 70 years found a 10% prevalence of OH, with two-thirds asymptomatic. Compared to those with symptomatic OH, participants with asymptomatic OH had a higher risk of unexplained falls (odds ratio (OR) 2.01 [CI 1.11, 3.65]; p=0.022) but not explained falls (OR 0.93 [CI 0.53, 1.62]; p=0.797) during follow-up. The third study revealed that those with OH and greater TSI drops on standing had the highest risk of future unexplained falls (OR 2.16 [CI 1.30 3.60]; p = 0.003). Finally, NIRS monitoring during HUT testing was shown to be a useful adjunct in the investigation and diagnosis of psychogenic pseudosyncope (PPS), an important form of apparent syncope. These findings provide important clinical implications for the assessment of falls in older people with OH particularly those with asymptomatic OH and in those with marked cerebral hypoperfusion on standing. NIRS-derived TSI measurements of CBF can identify those with OH at highest risk of future unexplained falls and aid in the diagnosis of PPS.
APPROVED
Keywords: orthostatic hypotension; cerebral perfusion; falls; near-infrared spectroscopy; cerebral oxygenation; cerebral blood flow; syncope